Circular biomanufacturing through harvesting solar energy and CO2. (July 2022) - Sørensen, Mette; Andersen-Ranberg, Johan; Hankamer, Ben; Møller, Birger Lindberg
Abstract : Using synthetic biology, it is now time to expand the biosynthetic repertoire of plants and microalgae by utilizing the chloroplast to augment the production of desired high-value compounds and of oil-, carbohydrate-, or protein-enriched biomass based on direct harvesting of solar energy and the consumption of CO2 . Multistream product lines based on separate commercialization of the isolated high-value compounds and of the improved bulk products increase the economic potential of the light-driven production system and accelerate commercial scale up. Here we outline the scientific basis for the establishment of such green circular biomanufacturing systems and highlight recent results that make this a realistic option based on cross-disciplinary basic and applied research to advance long-term solutions. Highlights: Earth receives 5000× more solar energy than required to power the entire global economy. The biosynthetic capacity of the chloroplast and catalytic versatility of P450 enzymes enables sustainable production of numerous high-value compounds and bulk products. The global supply of low-emission fuels may be supplied by microalgae grown on floating ocean platforms covering 0.2–0.3% of Earth's surface. Development of environmentally benign photosynthesis-based advanced production systems build on cross-disciplinary research, open mindedness, and a willingness to share will foster biophilicity and thus increase societal awareness of nature. Researchers, governments, and industry have the tools in place to power a sustainable solar biotechnology (Я)evolution. Knowledge-based political leadership is now critical to support scale up and ensure economic, social, and environmental security.